Investigations of solution-processed charge generation unit with low concentration of small molecule doped in p-type/HAT-CN6 for tandem OLED - Talik N.A.; Yeoh K.H.; Ng C.Y.B.; Tan C.Y.; Yap B.K. (Elsevier B.V., 2023)
Capacitance; Molecules; Capacitance voltage; Charge generating layer; Electrical measurement; Energy-band diagram; Injection mechanisms; Performance improvements; Poly(N-vinylcarbazole); Solution processable; Organic light emitting diodes (OLED)